Selective Thermotolerant Lactic Acid Bacteria Isolated From Fermented Juice of Epiphytic Lactic Acid Bacteria and Their Effects on Fermentation Quality of Stylo Silages - Pitiwittayakul, Nittaya; Bureenok, Smerjai; Schonewille, Jan Thomas (Frontiers in Microbiology, 2021)
The aim of the present study was to isolate and identify lactic acid bacteria (LAB) from fermented juice of tropical crops such as Napier grass, Ruzi grass, Purple guinea grass, Stylo legume, and Leucaena and their application to improve the quality of tropical crop silage. Fifteen strains of LAB were isolated. The LAB strains were Gram-positive and catalase-negative bacteria and could be divided into three groups, i.e., Pediococcus pentosaceus, Lactiplantibacillus (para)plantarum, and Limosilactobacillus fermentum according to the biochemical API 50CH test. Based on the analysis of 16S rRNA sequence, the strains isolated in the group L. (para)plantarum were distinguished. Two isolates (N3 and G4) were identified as Lactiplantibacillus plantarum. Three isolates (St1, St2, and St3) were identified as L. paraplantarum. In addition, the identification of other isolates was confirmed in the group P. pentosaceus (R1, R4, R5, R8, R11, and L1) and the group L. fermentum (N4, G6, G7, and N4). All selected strains were able to grow at 50°C. All LAB strains showed antimicrobial activity against Escherichia coli ATCC 25922, Shigella sonnei ATCC 25931, Pseudomonas aeruginosa ATCC 27853, and Bacillus cereus ATCC 11778. Four selected LAB strains (St1, St3, N4, and R4) were tested for their capacity to successfully ensile Stylo legume (Stylosanthes guianensis CIAT184). Stylo silages treated with LAB were well preserved, the NH3–N and butyric acid contents were lower, and the lactic acid content was higher than those in the control (p < 0.05). The acetic acid content was the highest in R4-treated silage among the treatments (p < 0.05). The crude protein (CP) content of St1-silage was significantly (p < 0.05) higher than the others. The inoculation of thermotolerant LAB selected from fermented juice of epiphytic lactic acid bacteria (FJLB) was found to be highly instrumental to obtain well-preserved silage from the Stylo legume.